Darwin Versus Wallace: Esthetic Evolution and Preferential Mate Choice - Davis, Adam C.; Arnocky, Steven (Frontiers in Psychology, 2022)
Dominant theorizing and research surrounding the operation of intersexual selection in evolutionary psychology tends to be guided by an adaptationist framework and aligned with models of sexual selection involving direct benefits (e.g., parental care) and indirect “good gene” and condition-dependent benefits. In this way, evolutionary psychologists more often espouse Alfred Russel Wallaces’ utilitarian viewpoint that traits become attractive because they honestly signal vigor and vitality, which gives priority to natural selection. In doing so, Darwin’s aesthetic perspective originally articulated in The Descent of Man and alternative models of sexual selection (e.g., Fisherian runaway), are given less consideration. This is despite some informative reviews on the topic in evolutionary psychology. In the current conceptual analysis, we discuss the potential of Prum’s Lande–Kirkpatrick (LK) null model of sexual selection to help make sense of some of the mixed evidence regarding the links between attractive traits and purported markers of phenotypic and genetic condition. We then consider how the implications of the LK null can help to shift theoretical assumptions and guide future work in evolutionary psychology on intersexual selection.